Morpholine As a Scaffold in Medicinal Chemistry: An Update on Synthetic Strategies - Tzara, Ariadni; Xanthopoulos, Dimitrios; Kourounakis, Angeliki P. (ChemMedChem, 2020)
Morpholine is a frequently used heterocycle in medicinal chemistry and a privileged structural component of bioactive molecules. This is mainly due to its contribution to a plethora of biological activities as well as to an improved pharmacokinetic profile of such bioactive molecules. The synthesis of morpholines is a subject of much study due to their biological and pharmacological importance, with the last such review being published in 2013. Here, an overview of the main approaches toward morpholine synthesis or functionalization is presented, emphasizing on novel work which has not been reviewed so far. This review is an update on synthetic strategies leading to easily accessible libraries of bioactives which are of interest for drug discovery projects. Privileged heterocycle: This review is an update on synthetic strategies leading to easily accessible libraries of morpholine‐containing bioactives which are of interest in drug discovery projects. An overview of the main approaches toward morpholine ring forming reactions or ring functionalization, is presented herein as one of the medicinal chemistry aspects of morpholine (bioactive) derivatives. The emphasis is on novel work which has not been reviewed so far.